APLIKASI AUDIT INTERNAL KOPERASI MITRA DHUAFA - Wisnu Ramdhani; Mina Ismu Rahayu (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2018)
The presence of computer technology with the power of the process has enabled the development of internal applications for computer-based audits at Koperasi Mitra Dhuafa. This application is an application that is made to simplify the activity process for the internal audit division at Koperasi Mitra Dhuafa, because there are many internal audit team activities that are under control and still need to be addressed. In this study a soft role has been developed that has the ability to control and fix things that are still lacking in internal audit activities, such as schedule control, management of findings and storage of report files. The methodology used for software development with the Waterfall method includes system engineering, analysis, design, coding, targeting and maintenance. The data collection methodology carried out is literature study techniques, observation and interviews with Auditor staff and Audit Managers. This application serves to facilitate the audit team to conduct audit scheduling, manage audit findings, and store results or audit reports. The benefits of making this internal audit application include facilitating the manager audit and Auditor staff as the audit executor in the process of its activities.